DDRE-04. EFFECTIVENESS AND SAFETY OF OSIMERTINIB FOR PATIENTS WITH LEPTOMENINGEAL METASTASES FORM NON-SMALL CELL LUNG CANCER: A SYSTEMATIC REVIEW AND META-ANALYSIS. (12th November 2021) - Wen, Lei; Shan, Changguo; Wang, hui; Yang, yanying; Ye, Minting; Hong, Weiping; Cai, Linbo
Abstract: BACKGROUND: the FLAURA study established Osimertinib to be the priority choice for the treatment of metastatic non-small cell lung cancer (NSCLC) harboring mutated epidermal growth factor receptor (EGFR). However, like many previous studies, the FLAURA study excluded patients with symptomatic CNS metastases. Hence, we performed a systematic review and meta-analyses of studies to assess the efficiency and safety of Osimertinib for the treatment of NSCLC with leptomeningeal metastases (LM). METHODS: We included studies published between 2010 and 2021 that evaluated the efficacy and toxicity of Osimertinib in NSCLC patients with LM. We searched PubMed, Embase, and oncology meeting abstracts (ASCO, ESMO and WCLC). Primary outcomes were objective response rate (ORR), disease control rate (DCR), any grade 3/4 toxicity rate. We used the random-effects model to generate pooled estimates for proportions. Newcastle-Ottawa Scale (NOS) was used to assess the certainty in the evidence. RESULTS: Twelve studies reporting on 367 patients were included in the meta-analysis. Most patients (≥90%) received Osimertinib as at least second line of treatment. The objective response rate was 42% (95% CI, 24%-59%; n = 184), and CNS disease control rate was 90% (95% CI, 85%-94%; n = 154). Intracranial progression free survival and overall survival ranged from 3.7 to 15.6 months, and 11.0 to 18.8 months, respectively. Adverse events were similar with previous studies and Common Terminology Criteria for Adverse Events (version 3.0) grade 3 or higher adverse event rates was acceptable. CONCLUSION: This meta-analysis confirmed that for advanced NSCLC with LM harboring EGFR-TKI-sensitizing mutations, Osimertinib showed impressive antitumor activity and acceptable toxicity.